Benzofuran Substituted Chalcone Derivatives Trigger Apoptotic Cell Death Through Extrinsic Pathway in Human Lung and Breast Cancer Cells - Alioglu, Imren; Cinar-Asa, Sibel; Coskun, Demet; Ari, Ferda (Springer Int Publ Ag, 2023)
In this study, the anticancer potential of benzofuran-substituted chalcone derivatives Compound 1 [(3-(Benzofuran-2-yl) -5-(4-N, N-dimethylaminophenyl)-2-pyrazoline)], Compound 2 [(4) -((1E)-3-(1)-benzofuran-2-yl)-3-oxoprop-1-en-1-yl]-2-methoxyphenylchloroacetate), Compound 3 [(3-(Benzofuran-2-yl)) -5-(thiophen-2-yl)-2-pyrazoline)] and Compound 4 [3-[(1E)-3-(1-benzofuran-2-yl)-3-oxoprop-1-en-1-yl)] phenyl chloroacetate) was investigated. Their cytotoxic and apoptotic effects were explored on the human breast (MCF-7 and MDA-MB-231) and lung (A549 and H1299) cancer cells by SRB and ATP cell viability assays and Hoechst 33342/Propidium Iodide dual staining. Expressions of proteins were examined by Western blot, and cell migration test was performed for metastatic effect. In conclusion, it has been shown that Compounds 2 and 4 have high cytotoxic activity on both human breast MCF-7 (IC50:9.37-2.71) and MDA-MB-231 (IC50:5.36-2.12) and lung A549 (IC50:3.23-2.21) and H1299 (IC50:6.07-2.92) cancer cell lines respectively. In addition, it has been found that Compounds 2 and 4 induce apoptosis via extrinsic pathway in the cells. Besides, they inhibited the migration of the cells showing antimetastatic potential.
Keywords: Chalcone; Benzofuran; Breast cancer; Lung cancer; Apoptosis; Cytotoxicity